Reading as a Predictor of Complex Syntax. The Case of Relative Clauses - Cilibrasi, Luca; Adani, Flavia; Tsimpli, Ianthi (Frontiers in Psychology, 2019)
Background: The current study aims at better characterizing the role of reading skills as a predictor of comprehension of relative clauses. Well-established cross-linguistic evidence shows that children are more accurate in the comprehension of subject-extracted relative clauses in comparison to the object-extracted counterpart. Children with reading difficulties are known to perform less accurately on object relatives at the group level compared to typically developing children. Given that children’s performance on reading tasks is shown to shape as a continuum, in the current study we attempted to use reading skills as a continuous variable to predict performance on relative clauses. Methods: We examined the comprehension of relative clauses in a group of 30 English children (7-11 years) with varying levels of reading skills. Reading skills varied on a large spectrum, from poor readers to very skilled readers, as assessed by the YARC standardised test. The experimental task consisted of a picture-matching task. Children were presented with subject and object relative clauses and they were asked to choose one picture - out of four - that would best represent the sentence they heard. At the same time, we manipulated whether the subject and object nouns were either matching (both singular or both plural) or mismatching (one singular, the other plural) in number. Results: Our analysis of accuracy shows that subject relatives were comprehended more accurately overall than object relatives, that responses to sentences with noun phrases mismatching in number were more accurate overall than the ones with matching noun phrases and that performance improved as a function of reading skills. Within the match subset, while the difference in accuracy between subject and object relatives is large in poor readers, the difference is reduced with better reading skills, almost disappearing in very skilled readers. Discussion: Beside replicating the well-established findings on the subject-object asymmetry, number facilitation in the comprehension of relative clauses and a better overall performance by skilled readers, these results indicate that strong reading skills may determine a reduction of the processing difficulty associated with the hardest object relative clause condition (i.e., match), causing a reduction of the subject-object asymmetry.